2015
DOI: 10.1038/hdy.2015.37
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and validation of a major QTL affecting resistance to pancreas disease (salmonid alphavirus) in Atlantic salmon (Salmo salar)

Abstract: Pancreas disease (PD), caused by a salmonid alphavirus (SAV), has a large negative economic and animal welfare impact on Atlantic salmon aquaculture. Evidence for genetic variation in host resistance to this disease has been reported, suggesting that selective breeding may potentially form an important component of disease control. The aim of this study was to explore the genetic architecture of resistance to PD, using survival data collected from two unrelated populations of Atlantic salmon; one challenged wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 55 publications
5
72
0
1
Order By: Relevance
“…Similar results were also reported in other aquatic species for disease resistance, such as QTL in Atlantic salmon40, turbot363738, eastern oyster ( Crassostrea virginica )41 for resistance against viruses, bacteria and parasites. However, we also noticed that several studies reported major QTL for resistance to infectious pancreatic necrosis (IPN) virus424344 and salmonid alphavirus45, explaining up to 50% phenotypic variation, in Atlantic salmon. Due to their large effect on the trait, these QTL have already been applied in MAS in Atlantic salmon, greatly reducing the economic losses of the salmon industry46.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Similar results were also reported in other aquatic species for disease resistance, such as QTL in Atlantic salmon40, turbot363738, eastern oyster ( Crassostrea virginica )41 for resistance against viruses, bacteria and parasites. However, we also noticed that several studies reported major QTL for resistance to infectious pancreatic necrosis (IPN) virus424344 and salmonid alphavirus45, explaining up to 50% phenotypic variation, in Atlantic salmon. Due to their large effect on the trait, these QTL have already been applied in MAS in Atlantic salmon, greatly reducing the economic losses of the salmon industry46.…”
Section: Resultsmentioning
confidence: 72%
“…In addition, mapping QTL in multi-family would allow precise mapping as the LD block is smaller and cross-validation of these QTL to reduce the false positives. This was demonstrated in Atlantic salmon, as most of these studies were performed on multi-family43444547. Therefore, future studies should focus on QTL mapping on multi-family using GBS, which could allow detection of common QTL for resistance to VNN in Asian seabass.…”
Section: Resultsmentioning
confidence: 99%
“…) and salmonid alphavirus (SAV) resistance (Gonen et al . ). Like for IPNV, the IHNV QTLs explained a high part of the phenotypic variance (up to 32.5% according to Barroso et al .…”
Section: Selective Breeding To Nnv Resistance: Prospective Proceduresmentioning
confidence: 97%
“…Recent developments in genomic tools and their application in animal breeding have opened new opportunities to understand the underlying genetic basis of commercially important traits and how to exploit them in breeding programmes. For example, QTLs (quantitative trait loci) have been identified and validated for a variety of traits including growth (Baranski, Moen, & Vage, ; Tsai, Hamilton, Guy et al., ; Tsai, Hamilton, Tinch et al., ), susceptibility to pancreatic disease (Gonen et al., ), susceptibility to infectious pancreatic necrosis (Houston et al., ; Moen, Baranski, Sonesson, & Kjoglum, ) and survival in the wild (Besnier et al., ). Furthermore, genomewide association studies identified single genes that influence important phenotypes, such as the vgll3 locus acting on age of maturation in adult salmon (Ayllon et al., ; Barson et al., ).…”
Section: Geneticsmentioning
confidence: 99%